The Abilities of Bacillus subtilis and Trichoderma sp. to Suppress Powdery Mildew Disease on Tomato Leaves - Istifadah, Noor; Maharani, Febry Aulia Riski (CROPSAVER, 2023)
Powdery mildew caused by Oidium sp. is an important disease on tomatoes cultivated in the greenhouse. Biological control is an environmentally-friendly method for plant disease control. The objective of this study was to examine the abilities of Bacillus subtilis and Trichoderma sp. isolated from compost tea to suppress powdery mildew disease on tomato leaves. The experiments were arranged in randomized complete block design with seven treatments consisting application of B. subtilis, Trichoderma sp., the combination of both microbes, molasses (1%), water and control (untreated leaves). In the first experiment, the treatments were applied on the infected leaves as curative strategy, while in the second experiment the treatments were applied at 7, 4, and 1 day before and every 3 days after pathogen inoculation. The results showed that B. subtilis, Trichoderma sp. or combination of both microbes that were applied in the infected leaves only reduced the disease severity by 29–33%. However, the application of B. subtilis every three days started at 7 days before pathogen inoculation suppressed powdery mildew by 93.7%, whereas combination of B. subtilis and Trichoderma sp. reduced the symptom on inoculated leaves by 85.3%. Spraying tomato leaves with 1% molasses reduced the infection rate and suppressed powdery mildew by 78.6%. Mixing the molasses with Trichoderma sp. suspension (10%, v/v) did not improve the level of suppression. This study showed that application of B. subtilis regularly as preventive measure is very potential for biological control of powdery mildew disease.